The progress of olfactory ensheathing cells in the treatment of brain ischemia. Issue 1 (28th March 2018) - Zhang, Chao
Abstract : Brain ischemia is commonly encountered in clinical practice, and the treatment strategies for brain ischemia were limited. Olfactory ensheathing cells (OECs), as important glial cells, are available to the transplantation for the treatment of brain ischemia. A few studies confirmed that OEC administration could reduce the volume of infarct, promote neurological function recovery and nerve regeneration in rats with bran ischemia. OEC can express several trophic factors in vitro culture, and cell cultures can be regulated by using certain nutritional factors such as vascular endothelial growth factor ( VEGF ), insulin like growth factor‐1 ( IGF‐1 ), and brain‐derived neurotrophic factor ( BDNF ). Additionally, other cultured nerve cells have a similar effect. These findings suggest neurotrophic factors (NTFs) may mainly contribute to the effect of OEC administration. However, there are still some problems on OEC transplantation for the treatment of brain ischemia. The objective of this review is to evaluate the current situation of OEC administration in brain ischemia, and discuss some problems on the clinic use of OEC for the treatment of cerebral ischemia.